KINERJA KARYAWAN DAN FAKTOR-FAKTOR DETERMINANNYA - Ika Khoirul Islamiyah; Aprih Santoso; Nirsetyo Wahdi (Pusat Riset dan Inovasi Nasional, 2021)
The problem in this research is the employees of PT Wiraswasta Gemilang Indonesia Cab. Semarang was not able to achieve the target set by PT Wiraswasta Gemilang Indonesia Cab. Semarang and this study aims to analyze the variables of leadership style, work environment, work stress and workload on the performance of employees of PT Wiraswasta Gemilang Indonesia Cab. Semarang. The population in this study were all employees of PT Wiraswasta Gemilang Indonesia Cab. Semarang, totaling 68 employees, while the sampling technique used is the census technique and the analytical tool used in this study is multiple linear regression. The results showed that the variables of leadership style, work environment, work stress and workload had an effect on the performance of employees of PT Wiraswasta Gemilang Indonesia Cab. Semarang.